2015
DOI: 10.1038/srep11395
|View full text |Cite
|
Sign up to set email alerts
|

Monolithic Magneto-Optical Nanocomposites of Barium Hexaferrite Platelets in PMMA

Abstract: The incorporation of magnetic barium hexaferrite nanoparticles in a transparent polymer matrix of poly(methyl methacrylate) (PMMA) is reported for the first time. The barium hexaferrite nanoplatelets doped with Sc3+, i.e., BaSc0.5Fe11.5O12 (BaHF), having diameters in the range 20 to 130 nm and thicknesses of approximately 5 nm, are synthesized hydrothermally and stabilized in 1-butanol with dodecylbenzenesulfonic acid. This method enables the preparation of monolithic nanocomposites by admixing the BaHF suspen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(18 citation statements)
references
References 29 publications
(35 reference statements)
0
17
0
Order By: Relevance
“…Barium hexaferrite (BaFe12O19, BHF) nanoplatelets are a classic example of this type of magnetic structure. 1,16 The BHF crystalizes in a magnetoplumbite structure that can be represented as a hexagonal close-packed stacking of oxygen and barium ions with smaller iron ions positioned at the interstitial sites. The structure can be subdivided into two alternating structural blocks stacked along the c-direction: a hexagonal "R" block ((BaFe6O11) 2-) and a cubic "S" block ((Fe6O8) 2+ ) 17,18 (Fig.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Barium hexaferrite (BaFe12O19, BHF) nanoplatelets are a classic example of this type of magnetic structure. 1,16 The BHF crystalizes in a magnetoplumbite structure that can be represented as a hexagonal close-packed stacking of oxygen and barium ions with smaller iron ions positioned at the interstitial sites. The structure can be subdivided into two alternating structural blocks stacked along the c-direction: a hexagonal "R" block ((BaFe6O11) 2-) and a cubic "S" block ((Fe6O8) 2+ ) 17,18 (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…15 This has led to the use of BFH in diverse applications such as ferromagnetic liquid crystals 3,22 and magneto-optical composites. 1 These applications of hard-magnetic nanoplatelets are very encouraging; however, they also revealed that a further improvement in their MS is necessary. An alternative approach to enhance MS in hard-magnetic materials is the exchange coupling low-MS materials (e.g., BHF) with high-MS softmagnetic materials.…”
Section: Introductionmentioning
confidence: 99%
“…Figure 9 shows the UV-vis spectra of the NPLs-Si, gold, and Janus NPL particles prepared in this work and dispersed in water. NPLs-Si (Figure 9a) show a broad absorption below 600 nm, which is the strongest at 300-400 nm and originates from the core BHF NPLs [66]. The Au nanoparticles show typical absorption at around 530 nm due to the surface plasmon resonance (Figure 9b) [67].…”
Section: Janus Bhf Nplsmentioning
confidence: 99%
“…5 Inspired by the anisotropic architectures of the natural materials, people are committed to developing new materials that contain aligned particles. [6][7][8][9] These materials can exhibit enhanced magnetic, mechanical, optical, and diffusive (heat and mass) properties. For example, soft magnetic composites, consisting of magnetic particles embedded in an insulating matrix, have great potential for a variety of breakthrough applications, including magneto-optics, 10 biological tissue scaffolds, 11,12 drug targeting, 13 and high-frequency applications such as microwave absorption, electromagnetic shielding, 14 inductors, and antennae.…”
Section: Introductionmentioning
confidence: 99%